Effects of diethyidithiocarbamate (DETC) on liver injury induced by ischemia-reperfusion in rats - Maio, R. (2015)
Purpose. In organ transplantation, ischemia-reperfusion injury (I/R) is a constant occurrence. Dithiocarbamates, a class of antioxidants, have been reported to inhibit nuclear factor-kappa B (NF-kappa B), a critical transcription factor in the intracellular inflammatory cascade. We studied the effects of diethyldithiocarbamate (DETC) on liver injury induced by I/R. Materials and methods. Male Wistar rats were pretreated with DETC (100 mg/kg IV) 10 minutes before hepatic ischemia, which was followed by 2 hours reperfusion, or 10 minutes prior to the reperfusion. Blood samples were obtained at the end of the reperfusion period to determine the biochemical markers of liver injury. Results were compared using the one-way analysis of variance (ANOVA), followed by the Bonferroni posttest, and presented as mean values +/- SEM. Results. I/R produced significant increases in aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), and gamma-glutamyl transferase (gamma-GT) serum levels compared with sham-operated rats. Administration of DETC prior to the onset of reperfusion significantly reduced the liver injury. However, DETC administered before the ischernic period failed to protect the liver from an I/R injury. Conclusion. DETC, administered just before the reperfusion period, resulted in a significant decrease in the I/R injury to the liver, an observation that may have therapeutic implications.